THE RELATIONSHIP BETWEEN BURNOUT AND NURSES’ PERFORMANCE IN THE EMERGENCY DEPARTMENT OF PROF. DR. MARGONO SOEKARJO HOSPITAL - Pratami, Leny Desti; Fitriana, Nurul Fatwati; Endiyono, Endiyono; Setiyabudi, Ragil (Universitas Kadiri, 2025)
Burnout is a condition of physical, emotional, and mental exhaustion caused by excessive work demands. Emergency Department (ED) nurses are at high risk of burnout due to heavy workloads and intense emotional pressure, which may affect their performance. This study aimed to determine the relationship between burnout and nurses’ performance in the Emergency Department of Prof. Dr. Margono Soekarjo Hospital. This research used a quantitative approach with a descriptive analytic design and a cross-sectional method. The sample consisted of 45 ED nurses selected using a total sampling technique. The instruments used were the Malach Burnout Syndrome (MBS) questionnaire for burnout and a performance assessment questionnaire for nurses’ performance. Data were analyzed using descriptive statistics and the Chi-Square test. The findings showed that most respondents experienced mild burnout (88.9%) and had high performance (88.9%). The Chi-Square test indicated a significant relationship between burnout and nurses’ performance (p = 0.01). Conclusion: Lower levels of burnout are associated with higher performance. These results emphasize the importance of preventing burnout to maintain the quality of nursing care in the Emergency Department. Keywords: burnout, nurses’ performance, emergency department, work fatigue